Temperature distribution and entropy generation during Darcy–Forchheimer–Brinkman electrokinetic flow in a microfluidic tube subject to a prescribed heat flux - Misra, J. C.; Mallick, B.; Steinmann, P. (Meccanica (Milan), 2020)
Electrokinetically modulated flow through a hydrophobic microtube embedded in a Darcy–Forchheimer porous medium is investigated in this paper. The steric effect has been taken into account in the electrical double layer (EDL) region. Heat transfer is analysed in the case of Darcy–Forchheimer–Brinkman flow subject to Joule heating. The flow is supposed to take place under the combined influence of electroosmosis and imposed pressure gradient. The governing nonlinear partial differential equations for electric potential, fluid flow and heat transfer are solved numerically by developing an iterative finite difference method that has second order accuracy. The thermal efficiency is discussed under the purview of the second law of thermodynamics. Influences/impact of different physical parameters on velocity, temperature and entropy are investigated and demonstrated graphically. The paper shows that with an increase in the steric effect, the electrokinetic velocity diminishes and that thermal irreversibility is very high in the electrical double layer region, but it reduces drastically in the neighbourhood of the central region of the microtube. Results of the study are likely to be of profuse interest in the design and development of microfluidic devices that deal with critical types of fluid transport mechanism in non-Darcian porous media.